THE ROLE OF THE HEREDITARY PREDISPOSITION IN THE DEVELOPMENT OF AORTA COARCTATION - T. N. Tatarinova; A. A. Kostareva; E. V. Grekhov; O. M. Moiseeva ("Paediatrician" Publishers LLC, 2012)
As a result of examination of the families of patients with aorta coarctation the factors predisposing to this condition were established. Sixty eight patients with different localization, stenosis degree and extent of aorta coarctation were included into this study. All the patients were performed echocardiography, indirect and direct. Typical coarctation was found in 95,6% of the cases, in 55,9% it was associated with bicuspid aortic valve. The most significant predisposing factors to this anomaly development were compromised hereditary (33,8%) and complications during pregnancy (57,4%). According to the received data, during the family planning it is important to examine both parents, as father's disorders may have more marked impact on aorta coarctation development, than mother's ones. Children with compromised heredity on congenital heart defects are recommended to be carried out echocardiographic investigation at the early period of time after birth, despite the absence of disorders on intrauterine ultrasound.